Evaluation of Acid Attack on Concrete Containing Spent Garnet as Partial Sand Replacement - Chong, Yee Hau; Mokhatar, Shahrul Niza; Albshir Budiea, Ahmed Mokhtar (Recent Trends in Civil Engineering and Built Environment, 2022)
This research studied the water absorption of concrete containing spent garnet and determine the durability of concrete containing spent garnet in acidic environment. The materials used along the experiment works were spent garnet, river sand, crushed stone, ordinary Portland cement and water. In this study, spent garnet were used as sand replacement with 0%, 10%, 20%, 30% and 40% in concrete mix designs. First and foremost, the water absorption test was conducted on 3 set of water-curing cube specimens with dimension 100 mm cube for the plain concrete and for each percentage of spent garnet concrete mixes and was done in compliance with the BS 1881: Part122 (1983) specification. After that, the durability tests under 5% of hydrochloric acid attack and 5% of sulphuric acid attack were conducted by preparing corresponding sets of concrete specimens which were 3 set of 28 days water-curing specimens for each percentage of spent garnet in different acid immersion according to Standard ASTM C1898 – 20 while the compressive strength was under standard in BS EN:12390-3: 2019. In the end of the study, the physical appearances of the samples were observed and the weight loss for each sample was tested and recorded accordingly. From the results obtained, the highest percentage of water absorption of concrete was C20 which was 7.80 %. However, the stronger average concrete strength of concretes from both acids with the achieved target compressive strength was concrete C20 but also with lowest weight loss. The concrete containing with 20 % of spent garnet had better acid resistant in terms of visual assessment not only toward sulphuric acid attack but also toward hydrochloric acid attack. The application of 20 % of spent garnet as sand replacement was hence can provide stronger acid resistant in maintaining the supporting strength of concrete. As a suggestion, the durability of normal concrete should be investigated over a longer length of time in order to mimic the real-world circumstance in which a structure is erected.